Pemberdayaan Unit Usaha BUMD di Desa Kedungdowo Kecamatan Ploso - Achmad Kautsar; Dewie Tri Wijayati; Hafid Kholidi Hadi; Trias Madanika Kusumaningrum; Hujjatullah Fazlurrahman (Inspirasi Nusantara, 2022)
Kedungdowo Village has a village-owned business entity with the name BUMDes Tumbuh Lestari. Those who have business units include the Savings and Loans Unit and are currently developing, the second is the village market, and the third is a heavy equipment rental unit. The challenges during the Covid pandemic have hampered the performance of BUMD. Therefore, it is important to empower through training and mentoring to prepare BUMD to grow sustainably in order to survive during the pandemic with financial management and branding. Based on the results of the training and mentoring, it can be concluded that the material presented is easy to understand and easy to implement, as well as the outputs for preparing improved financial reports and food product branding grids that will be produced by BUMDs